Hermenêutica negra nos Estados Unidos - Nash, Peter T. (2013)
In the last decade a generation of Black biblicists identified with the practice of a Black biblical hermeneutics established itself in the United States. The study presents a description of the four basic characteristics of this hermeneutics, proposing that these could also be a contribution in the search for a Brazilian Black hermeneutics.